2021
DOI: 10.3390/molecules26164778
|View full text |Cite
|
Sign up to set email alerts
|

Screening Papaveraceae as Novel Antibiofilm Natural-Based Agents

Abstract: The antimicrobial properties of herbs from Papaveraceae have been used in medicine for centuries. Nevertheless, mutual relationships between the individual bioactive substances contained in these plants remain poorly elucidated. In this work, phytochemical composition of extracts from the aerial and underground parts of five Papaveraceae species (Chelidonium majus L., Corydalis cava (L.) Schweigg. and Körte, C. cheilanthifolia Hemsl., C. pumila (Host) Rchb., and Fumaria vaillantii Loisel.) were examined using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
(71 reference statements)
0
9
0
Order By: Relevance
“…Finally, the cytotoxicity against stomach-and liver-derived cells may be associated with an inflammatory response manifested by cytokine expression and release. In our previous study on lipopolysaccharide-stimulated human neutrophils [57], we found that several alkaloids (sanguinarine, berberine, chelidonine, and chelerythrine) contained in the extracts from both tested plants [56], depending on the specific concentrations, had a dual anti-inflammatory and pro-inflammatory effect. Hence, the inflammatory response of stomach and liver cells and tissues upon treatment with the antibacterial extracts should be considered in future studies, including in vivo models.…”
Section: Limitations and Future Perspectivesmentioning
confidence: 87%
See 1 more Smart Citation
“…Finally, the cytotoxicity against stomach-and liver-derived cells may be associated with an inflammatory response manifested by cytokine expression and release. In our previous study on lipopolysaccharide-stimulated human neutrophils [57], we found that several alkaloids (sanguinarine, berberine, chelidonine, and chelerythrine) contained in the extracts from both tested plants [56], depending on the specific concentrations, had a dual anti-inflammatory and pro-inflammatory effect. Hence, the inflammatory response of stomach and liver cells and tissues upon treatment with the antibacterial extracts should be considered in future studies, including in vivo models.…”
Section: Limitations and Future Perspectivesmentioning
confidence: 87%
“…However, as this potentially undesired effect was not actually studied, it opens an opportunity for further investigation into the mechanisms by which the pathogenic bacteria may cope with such combined therapeutics. Despite many reports on differences between microbial strains in sensitivity to plant extracts, no data were found in the literature on specific mechanisms that would confer the resistance against complex mixtures of natural products containing both alkaloids and polyphenols [56]. Certainly, this issue needs to be addressed in future research aiming at verification of whether H. pylori is able to develop resistance to these and other plant-derived antibacterials and what would be the potential mechanisms of it.…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%
“…The advanced technology created features of BNC that enable to use it in medicine and pharmaceutical industry as biotechnology-based products or biopharmaceutics. Our proof of concept based on the biotechnological process of cells immobilization, both plant and bacterial, on the cellulose carrier let to expose the antimicrobial and anti-inflammatory properties of plant metabolites even stronger than when used separately [ 34 ]. The carrier ( Figure 1 ) showed differences in physical properties ( Table 1 ) correlated with the biosynthesis time (3, 5 or 7 days).…”
Section: Discussionmentioning
confidence: 99%
“…Our earlier studies have shown that C. majus cell cultures are rich in polyphenolic compounds and isoquinoline alkaloids with confirmed antimicrobial and anti-inflammatory properties [ 8 , 10 , 11 ]. The major metabolites secreted by BNC-immobilized C. majus cells were chlorogenic acid, trans-caffeic acid and quercetin; all these compounds are known for their antimicrobial activity and all of them were found in the aerial parts of naturally growing C. majus [ 34 ]. One of our main concerns, with regard to the applicability of our work, was potential inflammatory effect which could be displayed by NC-type BNC carriers, containing live K. xylinus cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, quercetin has strong antioxidant, antibacterial and antiparasite properties (Yang et al, 2020); it also binds specifically to GyrB, a subunit of Escherichia coli DNA gyrase, inhibiting its ATPase activity (Plaper et al, 2003). Quercetin also has strong antimicrobial potential against planktonic bacteria as well as disrupting biofilm formation of Staphylococcus aureus, Pseudomonas aeruginosa and Candida albicans (Zielinska et al, 2021).…”
Section: Introductionmentioning
confidence: 99%